Effect of preemptive intramuscular diclofenac on minimal effective-dose bupivacaine saddle block for minor perianal surgeries - Roshdi R Al-metwalli; Alaa M Khidr; Summayah M Fallata; Hitham M A. Elsayed (Saudi Journal of Anaesthesia, 2022)
Background: Preemptive analgesics are commonly used to increase analgesic efficacy and patient satisfaction. The aim of this study was to evaluate the preemptive analgesic effect of intramuscular diclofenac on minimal effective dose spinal anesthesia for perianal surgeries. Materials and Methods: Fifty patients ASA I&II were divided randomly into two groups, control group (GC N = 25) and Diclofenac group (GD N = 25), both groups received saddle block with 5% hyperbaric bupivacaine 0.5 mL (2.5 mg). Thirty minutes before the saddle block, patients in GD received 75 mg (3 mL) diclofenac intramuscularly, whereas patients in GC received 3 mL saline intramuscularly. The differences in the time for the first analgesic request, postoperative analgesic consumption as well as, visual analog scale, were our primary outcomes. Results: Fifty patients (25 in each group) undergoing perianal surgery completed the study successfully. The time to the first request of analgesia was significantly longer in GD 511.8 (108.07) min. compared to the GC 179.56 (49.24) min with P = 0.00001, as well as the total consumption of rescue analgesic (tramadol hydrochloride) was significantly less in GD 66 (23.8) mg compared to 104 (28.5) mg in the GC with P = 0.00001. Conclusion: Preemptive intramuscular diclofenac sodium with minimal dose bupivacaine saddle block significantly minimized the postoperative analgesic consumption and delayed the first analgesia request after perianal surgery.